PENERAPAN METODE SEARCH ENGINE OPTIMIZER DALAM PENGEMBANGAN SISTEM INFORMASI MANUFAKTUR KITCHEN FACILITY ORDERING - Elly Antika; Nugroho Setyo Wibowo; Nanik Anita Mukhlisoh (Jurnal Teknologi Informasi dan Terapan, 2019)
STEEL GT is a manufacturing company in Denpasar Bali. In August 2006 set up a branch in Jember and become a central plant that produces goods Kitchen Facility. Initial problems that arise in business company that is not doing promotion GT. STEEL online so that customers of this company only certain people are already known, or through friends of people who are already known. Besides recording and ordering data necessary control less effective and efficient, because the data is not centralized and done manually. Therefore GT STEEL need a system that can help resolve the problem. So that made e-commerce websites GT STEEL with SEO marketing methods to assist in the marketing system and solve the problem of controlling the data on the GT STEEL reservations.